2015
DOI: 10.1523/jneurosci.2970-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptors within the Mesolimbic Dopamine System Mediate Alcohol Relapse Behavior

Abstract: Glutamatergic input within the mesolimbic dopamine (DA) pathway plays a critical role in the development of addictive behavior. Although this is well established for some drugs of abuse, it is not known whether glutamate receptors within the mesolimbic system are involved in mediating the addictive properties of chronic alcohol use. Here we evaluated the contribution of mesolimbic NMDARs and AMPARs in mediating alcohol-seeking responses induced by environmental stimuli and relapse behavior using four inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…The AMPA glutamate receptor subunit Gria1 specifically has been implicated in substance use (14, 15, 20, 21) and related neuropsychiatric disorders (17). Our data now provide new insight highlighting the important contribution of specific acetylation disturbances related to transcriptional alterations of striatal GRIA1 in human heroin abusers that is dynamically regulated with repeated use of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPA glutamate receptor subunit Gria1 specifically has been implicated in substance use (14, 15, 20, 21) and related neuropsychiatric disorders (17). Our data now provide new insight highlighting the important contribution of specific acetylation disturbances related to transcriptional alterations of striatal GRIA1 in human heroin abusers that is dynamically regulated with repeated use of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Cue-induced reinstatement of ethanol seeking was increased by positive allosteric modulation of AMPA receptors [29] and decreased by genetic deletion of the GluR-C AMPA subunit [30], further supporting a role for iGluRs. In addition, recent work has indicated that glutamate inputs to VTA DA neurons influence ethanol relapse through combined action at NMDA and AMPA receptors [31]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NMDAR inhibition within the NAc does strongly inhibit compulsion‐like alcohol consumption that is driven by NAc adaptations in non‐canonical NMDARs (Seif et al , ; see below). Furthermore, NAc NMDARs do not regulate cue‐induced alcohol reinstatement in rats (Backstrom & Hyytia ) or mice (Eisenhardt et al ). In contrast, pharmacological NMDAR inhibition or genetic NMDAR knockdown in direct pathway cells within the NAc strongly reduces the Alcohol Deprivation Effect, a model of relapse where consumption is greatly enhanced by protracted abstinence (Eisenhardt et al ).…”
Section: Nmdar Contributions To Alcohol Addictionmentioning
confidence: 99%
“…Furthermore, NAc NMDARs do not regulate cue‐induced alcohol reinstatement in rats (Backstrom & Hyytia ) or mice (Eisenhardt et al ). In contrast, pharmacological NMDAR inhibition or genetic NMDAR knockdown in direct pathway cells within the NAc strongly reduces the Alcohol Deprivation Effect, a model of relapse where consumption is greatly enhanced by protracted abstinence (Eisenhardt et al ). Overall, these studies suggest that NAc NMDARs are not required for simpler forms of intake, similar to what is observed for cocaine (see above), but are critical for states of higher motivation, including compulsion‐like drinking and the Alcohol Deprivation Effect.…”
Section: Nmdar Contributions To Alcohol Addictionmentioning
confidence: 99%
See 1 more Smart Citation